The possible inclusion of legal provisions in Islamic banking and finance: the case study of the Mozambican regulatory framework - Modan, Carino; Hassan, Rusni (Emerald Group Publishing Ltd., 2018)
Purpose: This paper aims to thoroughly examine the extent to which the current legal and regulatory framework is inclusive towards Islamic banking and finance (IBF) practices in the attempts to introduce IBF as a significant component in the Mozambique’s financial system. This is achieved by providing a critical review on the Mozambican current legal and regulatory framework including the court and arbitration system, as well as the country’s financial institutions law and regulations. Design/methodology/approach: The methodology used in this study is the qualitative approach. The analysis made is based on descriptive and analytical approach whereby the study examined and critically analysed the banking regulations in Mozambique with the purpose of finding the legal gap in the existing legal and regulatory framework that allows the introduction of IBF in the country. Findings: This study finds that whilst some legal provisions in the current legal and regulatory framework are conflicting with the Sharï’ah principles such as the definition of loans and the concept of interest, there is also a certain number of enabling features that can be immediately explored, including deposits (with no interest), leasing operations, investment funds or venture capital. Research limitations/implications: At present, to the best of the authors’ knowledge, this is the first attempt ever made to assess the compatibility of the existing Mozambican commercial laws with the Islamic principles hence identifying the challenges that might arise due to the implementation of IBF practices in Mozambique. Practical implications: This paper has several practical implications in the sense that it helps the financial market authorities in Mozambique to be able to foresee possible inclusion of provisions on Islamic transactions in the country’s existing financial regulations. Social implications: The contributions of this paper lie in the valuable recommendations made on the insertion of Islamic principles in the current regulatory framework as well as assisting in overcoming some of the conflicting aspects in medium to long term. Mozambique should explore and benefit from the experience and lessons learned by the neighbouring countries that have successfully adopted the IBF practice. It is recommended that the Central Bank should establish a “task force team”, comprising of multi-skilled professionals and experts in Islamic finance from various internal areas ranging from licensing to supervision together with Sharï’ah scholars and representatives from the Muslim Community, to study the required process for adoption of IBF in the country. Originality/value: There is no other study on IBF in Mozambique, particularly on legal and regulatory aspects.